Sparing of first dose effect of monovalent anti-CD3 antibody used in allograft rejection is associated with diminished release of pro-inflammatory cytokines. - Abbs, I; Clark, M; Waldmann, H; Chatenoud, L; Koffman, C; Sacks, S (1994)
The murine monoclonal antibody OKT3 is the best known of the anti-CD3 antibodies used for the prevention and treatment of renal allograft rejection. Use of this antibody is associated with improved graft outcome but it has a number of adverse effects thought to result from the massive release of pro-inflammatory cytokines. It has been postulated that OKT3 causes cytokine release because of cross-linking of CD3 molecules on the cell surface by bivalent anti-CD3 antibodies, such as OKT3, and the simultaneous binding of the Fc regions of these monoclonal antibodies to Fc receptors on other cells resulting in cell activation. Monovalent antibodies directed against the CD3 antigen should not, in theory, cause cell activation and cytokine release by this postulated mechanism. This study details the use of a monovalent anti-CD3 monoclonal antibody in the treatment of allograft rejection in five renal transplant recipients and documents the degree of TNF, IFN-g and IL6 release generated after antibody injection. Monovalent anti-CD3 monoclonal antibody reversed the rejection episode for which it was used and was well tolerated in all patients. TNF, IFN-g and IL6 measurement showed that little pro-inflammatory cytokine release occurred after this drug. It is likely that the relative lack of side-effects of monovalent anti-CD3 reflects the blunted release of pro-inflammatory cytokines. Monovalent anti-CD3 monoclonal antibody may be a useful addition to the reagents available to treat allograft rejection.